204k views
3 votes
PLS HELP
f(1) = -6
f(2) = -4
f(n) = f(n - 2) + f(n - 1)
f(3) =

PLS HELP f(1) = -6 f(2) = -4 f(n) = f(n - 2) + f(n - 1) f(3) =-example-1
User Slythic
by
4.8k points

2 Answers

1 vote

Answer:

f(3)=-10

Explanation:

Khan

User Bohbian
by
5.3k points
6 votes

Answer:

f(1) = -6

f(2) = -4

f(n) = f(n - 2) + f(n - 1)

=> f(3) = f(2) + f(1) = -6 + (-4) = -10

Hope this helps!

:)

User Angel Fraga Parodi
by
5.6k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.